2014
DOI: 10.5152/tjg.2014.4851
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of carcinoid tumor to the transplanted liver graft: A rare case report

Abstract: In this study, we present a rare case of gastrointestinal carcinoid tumor that metastasized to a transplanted liver graft. A 14-year-old female patient suffering from cryptogenic cirrhosis had undergone liver transplantation. The liver was received from a deceased donor. She presented to our clinic with complaints of abdominal pain, diarrhea, flushing, fatigue, and syncope four years after transplantation. On multislice computed tomography, multiple masses ranging from 1 cm to 4 cm in size were detected in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Recently, some researchers have reported that MSCs can differentiate into organ-specific cells in vivo when they were successfully engrafted in the injured organ (4,5). Some far-reaching immunomodulatory effects have also been observed in MSCs (6), and they can be used in allotansplantation without rejection (7,8). Therefore, MSCs may have beneficial therapeutic effects for liver transplantation (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers have reported that MSCs can differentiate into organ-specific cells in vivo when they were successfully engrafted in the injured organ (4,5). Some far-reaching immunomodulatory effects have also been observed in MSCs (6), and they can be used in allotansplantation without rejection (7,8). Therefore, MSCs may have beneficial therapeutic effects for liver transplantation (9).…”
Section: Introductionmentioning
confidence: 99%